An Analysis of Proportional Reasoning Ability of Secondary School Students on Opportunity Material Viewed from Gender Perspective - Kusnul Khotimah; Ali Shodikin (Program Studi Tadris Matematika IAIN Salatiga, 2021)
This study aims to analyze the proportional reasoning ability of junior high school level students in solving math problems between male and female students on the opportunity material. This type of research is qualitative research. The subjects in this study were students of class VIII who were selected through the purposive sampling technique. Data collection methods are tests and interviews. The instruments used were the math ability test (TKM), proportional reasoning test (TPP) and interviews. Data were analyzed using the interactive model of Miles and Huberman. The validity of the data was tested by means of triangulation. The results showed that in the opportunity material, the male student subject was able to reach the entire level stage and fulfil the characteristics of proportional reasoning, while the female student subject was only able to reach level 1, while at level 2, the subject was unable to recognize the problem situation given was a proportional situation, at levels 3, 4 and 5 are unable to use multiplicative strategies so that they do not fulfil the characteristics of proportional reasoning. The research results are expected to be considered in determining learning strategies so that students master mathematical competencies optimally.